2018
DOI: 10.1002/hyp.13264
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model for groundwater discharge to a coastal brackish lagoon based on seepage measurements (Ringkøbing Fjord, Denmark)

Abstract: Groundwater discharge to a brackish lagoon (Ringkøbing Fjord) was quantified with seepage meters along four transects perpendicular to the shore during four seasons in 1 year. The objectives were to develop a conceptual model of the spatiotemporal variability of seepage and how landscape characteristics and saltwater intrusion affect seepage fluxes. The electrical conductivity of the groundwater was measured in vertical sediment profiles up to 3 m below the lagoon bed to assess the effects of the freshwater-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…However, the groundwater flow with the associated nutrient input to the lagoon has not been researched. Previous groundwater-related research focused exclusively on the physical processes that determine the flow of groundwater to the lagoon [22,37], and the development of methodologies to help quantify water fluxes [38,45].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…However, the groundwater flow with the associated nutrient input to the lagoon has not been researched. Previous groundwater-related research focused exclusively on the physical processes that determine the flow of groundwater to the lagoon [22,37], and the development of methodologies to help quantify water fluxes [38,45].…”
Section: Study Areamentioning
confidence: 99%
“…The data collection aimed to characterize the hydrogeological properties, fluxes, and hydrochemistry, including: freshwater aquifer inland (Inland wells A and B), shallow part of the aquifer underneath the lagoon (sampling points 1-30), and groundwater-lagoon water fluxes. The area was investigated in previous studies [22,38], allowing the optimization of the placement of sampling points 1-30 and the requirements to complete field work. Sampling points 1-30 extended along a transect from the shoreline up to 40 m offshore, with small differences in the water depth of the lagoon (water depth of 30 to 50 cm).…”
Section: Field Campaignsmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation could be due to the shallow depth of the wells and the lagoons and therefore, the regional discharge of the aquifer to the coast did not impact the water level measurements neither the groundwater-surface water interactions. The low-permeability sediments deposited on the lagoon-aquifer interface could have greatly influenced seepage rates [40], as well as the presence of organic sediments observed in other locations [54,55]. These could be the causes of the low percentage of the net groundwater exchange obtained in the water balance.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is interested in evaluating the methods for quantifying SGD and its inherent spatial heterogeneity. Duque et al [7] recently showed that spatial heterogeneity in exchange fluxes was more important than temporal heterogeneity and highlighted the impact of a correct characterization of the spatial heterogeneity on the discharge estimations, so this study focuses on capturing SGD as a snapshot in time.…”
Section: Introductionmentioning
confidence: 99%